Disaster management - Gupta, Harsh K., 1942-; Indian National Science Academy (Hyderabad : Universities Press : Distributed by Orient Longman, 2003)
With reference to India.
Fakulti Agro-Industri dan Sumber Asli.
Includes bibliographical references and index.
Keywords: Emergency management -- India; Hazardous geographic environment -- India; Natural disasters -- India